How Managers Use Multiple Media: Discrepant Events, Power, and Timing in Redundant Communication - Leonardi, Paul M.; Neeley, Tsedal B.; Gerber, Elizabeth M. (Organization Science, 2012)
Several recent studies have found that managers engage in redundant communication; that is, they send the same message to the same recipient sequentially through two or more unique media. Given how busy most managers are, and how much information their subordinates receive on a daily basis, this practice seems, initially, quite puzzling. We conducted an ethnographic investigation to examine the nature of events that compelled managers to engage in redundant communication. Our study of the communication patterns of project managers in six companies across three industries indicates that redundant communication is a response to unexpected endogenous or exogenous threats to meeting work goals. Managers used two distinct forms of redundant communication to mobilize team members toward mitigating potentially threatening discrepant events—unforeseen disruptive occurrences during the regular course of work. Managers with positional power over team members reactively followed up on a single communication when their attempt to communicate the existence of a threatening discrepant event failed, and they determined that a second communication was needed to enable its joint interpretation and to gain buy-in. In contrast, managers without positional power over team members proactively used redundant communication to enroll team members in the interpretation process—leading team members to believe that they had come up with the idea that completion of their project was under threat—and then to solidify those interpretations. Moreover, findings indicate that managers used different types of technologies for these sequential pairings based on whether their motivation was simply to transmit a communication of threat or to persuade people that a threat existed. We discuss the implications of these findings for theory about, and the practice of, technologically mediated communication, power, and interpretation in organizations.